Effect of Green Azolla (Azolla pinnata) supplementation on milk production, constituents and fatty acids profile in mid-lactating Barbari goats - Kumar, Ravindra; Abraham, G; Jaiswal, Pranta; Verma, Arun Kumar (Indian Journal of Dairy Science, 2022)
An experiment was conducted at Animal nutrition experimental unit, ICAR-Central Institute For Research on Goats, Makhdoom Farah, Mathura from Jan-March 2020 to study the effect of fresh azolla supplementation in lactating goats reared under intensive system. Twelve mid lactating Barbari goats were divided into two groups (CON and SUPP) of six each. CON was control (fed with 500 g concentrate pellets/head/day and ad libitum gram straw) while goats in SUPP was supplemented with 250 gram fresh azolla (20gDM) / day) along with gram straw and concentrate pellet. Body weight changes, milk production and milk constituents was studied. Milk production at 0, 30, 60 days of experimental feeding was recorded for two consecutive days. The animals were matured so no effect on body weight was observed. There was around 20% improvement in milk production at different stage of lactation on supplementation of 250g fresh azolla in mid lactating goats. There was no statistically significant (P<0.05) difference between groups in per cent total solids, moisture, solid not fat (SNFs), pH, ash and protein content of the milk. Lower fat per cent was observed in SUPP group as compared to CON group of lactating goats. However milk fat per day was similar in both the group of lactating goats. There was no significant effect of azolla supplementation on different fatty acids, Short chain Fatty acids (SCFA), saturated fatty acids, Mono unsaturated fatty acids(MUFA) and Poly unsaturated fatty acids(PUFA) in lactating goats. Present study concluded that fresh azolla supplementation improved the milk production with no significant effect on milk composition and fatty acid profile in stall fed lactating goats.